Васильев Евгений Александрович, Ганюшкин Борис Владимирович, Ляхов Евгений Григорьевич, Собакин Вадим Константинович, Хлестов Олег Николаевич, Черниченко Станислав Валентинович (Московский журнал международного права, 1992)
.